Low test–retest reliability of a protocol for assessing somatosensory cortex excitability generated from sensory nerves of the lower back - Ehrenbrusthoff, Katja; Ryan, Cormac G.; Martin, Denis J.; Milnik, Volker; Dinse, Hubert R.; Grüneberg, Christian (Frontiers in Human Neuroscience, 2022)
In people with chronic low back pain (CLBP), maladaptive structural and functional changes on a cortical level have been identified. On a functional level, somatosensory cortical excitability has been shown to be reduced in chronic pain conditions, resulting in cortical disinhibition. The occurrence of structural and/or functional maladaptive cortical changes in people with CLBP could play a role in maintaining the pain. There is currently no measurement protocol for cortical excitability that employs stimulation directly to the lower back. We developed a protocol for the measurement of single pulse somatosensory evoked potential (SEP) waveforms and paired-pulse behavior (PPB) generated from sensory nerves of the lower back and quantified its test–retest reliability in a sample of 30 healthy individuals to gain insights into the normal variability of cortical responses, which could then be compared to results from people with CLBP. We investigated cortical excitability by measuring SEPs and PPB. PPB was defined as the ratio of the amplitude of the second cortical response (A2s) divided by the first cortical response (A1). A2s was determined by subtracting the response to single-pulse stimuli from the paired pulse stimuli response to account for linear superposition effects. The test–retest reliability of the protocol was very poor with no evidence of systematic bias but a high amount of random variability between sessions. There was no significant difference in the right side PPB for session 1 (Mean ratio A2s/A1 = 0.66, SD = 0.54) and session 2 (Mean ratio A2s/A1 = 0.94, SD = 1.56); mean session difference [(95% CI) = −0.44 (−1.23 to 0.34); t (22) = −1.17, p = 0.26]. The ICC3.1 (absolute agreement) for the outlier-removed right side PPB were 0.19 (95% CI: −0.84 to 0.66) and 0.43 for left side PPB (95% CI: −0.37 to 0.76). This finding potentially has wider implications for PPB protocols. If these findings were replicated in other groups and other nerves, it would question the validity of this measure more generally. However, these findings are restricted to healthy people and sensory nerves of the lower back and may not be generalizable.